The concept «Competition» in Biology and Ecology - Serdiuk N. I. (Scientific community of students, 2018)
the article examines definitions of the concept «Competition» given by several dictionaries. In the article much attention is given to its place in biology and ecology in particular. It describes in detail the types of interactions between organisms and their groups in the biosphere and focuses on the competition as a sub-type mentioning its forms and the main resources organisms compete for. It is shown that people as a species experience competition as well. The article is of interest to biology and ecology students, who would want to develop their understanding of the concept «Competition».
Keywords: экология; биология; конкуренция; биосфера; вид; дефиниция; организм; competition; популяция; biology; population; ecology; biosphere; definition; species; dictionary; organism